Metalloproteomics Approach to Analyze Mercury in Breast Milk and Hair Samples of Lactating Women in Communities of the Amazon Basin, Brazil - Cerbino, M. R.; Vieira, José Cavalcante Souza [UNESP]; Braga, C. P. [UNESP]; Oliveira, G. [UNESP]; Padilha, I. F. [UNESP]; Silva, T. M.; Zara, L. F.; Silva, N. J.; Padilha, P. M. [UNESP] (Springer Nature, 2018)
Mercury is a potentially toxic element that is present in the environment of the Brazilian Amazon and is responsible for adverse health effects in humans. This study sought to assess possible protein biomarkers of mercury exposure in breast milk samples from lactating women in the Madeira and Negro Rivers in the Brazilian Amazon. The mercury content of hair samples of lactating women was determined, and the proteome of breast milk samples was obtained using two-dimensional electrophoresis after protein precipitation with acetone. Mercury measurements of protein spots obtained via protein fractionation were performed by graphite furnace atomic absorption spectrometry (GFAAS), and it was observed that mercury is linked to proteins with molecular masses in the range of 14–26 kDa. The total mercury concentration was also determined by GFAAS in unprocessed milk, lyophilized milk, and protein pellets, with the purpose of determining the mercury mass balance in relation to the concentration of this element in milk and pellets. Approximately 85 to 97% of mercury present in the lyophilized milk from samples of lactating women of the Madeira River is bound in the protein fraction. From lactating women of the Negro River, approximately 49% of the total mercury is bound in the protein fraction, and a difference of 51% is bound in the lipid fraction.
Keywords: 2D-PAGE; Biomarkers of mercury exposure; GFAAS; Mercury in milk; Metallomics study